DAMPAK SHANGHAI COOPERATION ORGANIZATION (SCO) TERHADAP EKONOMI DAN POLITIK TURKI TAHUN 2012-2016 - Ridarta, Wimbi Julio; Iskandar, Irwan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This research review the Impact of SCO (Shanghai Cooperation Organization) on Turkish Economy and Politics. Turkey's interest in SCO seen as an attempt to achieve economic interests from international trade activities. SCO is used by Turkey as a forum to expand and diversify market which has been dominated by European countries In the process of forming SCO, positive developments towards economic regionalism began to be created among Central Asian, Tiongkok and Russian based on mutual trust, and cooperation. Economic Cooperation is one of the key cooperation sectors for SCO, although at first it seemed to be covered by high levels of cooperation in the security sector. This research has theoretically been build using the Neoliberal Institutionalism perspective. This type of research is qualitative research. Data presented on secondary data through literature studies such as books, internet and others. Result of this research is through SCO (Shanghai Cooperation Organization) has a positive impact on Turkish Economy and Politics. Many efforts have been made Turkey to join the European Union but Turkey has not been recognized as a member Turkey conflict with Greece related Cyprus problems becomes a Turkey barrier to join the European Union. Different The SCO that opens the door for Turkey to join as Dialogue Partner and Erdogan's desire to become a permanent member of SCO. Turkey was chosen to be a leader in SCO Energy Club activities. Turkey's economy increased after joining as a Dialogue Partner. It is expected to continue increase if Turkey's request to become a permanent member of SCO is accepted. Turki economy has increased and turkey economic cooperation in the field of export and import has increased as well as the welfare of the Turki community. Keywords: Shanghai Cooperation Organization, Economic and Politic